The Representation of Non-Heterosexuality in YouTube: Study on K-Pop Girl Group Music Video - Astrid Hidayanti Ananda Putri (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
Since the late 2000s, the Korean pop music industry (K-pop) has made significant progress outperforming the music industry of other countries. The abundance of South Korean media content showing the concept of “Girl Band” is engaging because of changes in gender representation in the Korean pop music industry. This study focuses on the representation of non-heterosexuality in the music videos of the K-Pop girl groups Mamamoo, Loona, and Red Velvet. The Music Video (MV) of the three girl bands shows other sexual orientations, as is often shown in the South Korean media. By observing the three music videos, the author found that South Korea has begun to represent several sexualities and genders that exist through the KPop industry. This study aims to analyze how the South Korean entertainment industry began to represent non-heterosexuality in the music video clips of K-Pop girl groups. The method used in the study uses a qualitative approach with semiotic analysis by John Fiske. The results of this study indicate the existence of a non-heterosexual ideology implied by the three girl groups through the content in the music video uploaded on the Youtube media platform